2021
DOI: 10.26522/ssj.v15i3.2546
|View full text |Cite
|
Sign up to set email alerts
|

From Data Ethics to Data Justice in/as Pedagogy (Dispatch)

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…FAccT must also respond to contemporary and historical struggles against oppression by engaging in critical reflection and by re-centering its organizing principles and work [15,17,34,70] toward political action [27,48,65], resistance [30,68], and justice [14]. Venues such as FAccT would better serve the aims of AI ethics by embracing an "agonistic" approach to discourse, both within its research subjects and in its organizing principles.…”
Section: Discussionmentioning
confidence: 99%
“…FAccT must also respond to contemporary and historical struggles against oppression by engaging in critical reflection and by re-centering its organizing principles and work [15,17,34,70] toward political action [27,48,65], resistance [30,68], and justice [14]. Venues such as FAccT would better serve the aims of AI ethics by embracing an "agonistic" approach to discourse, both within its research subjects and in its organizing principles.…”
Section: Discussionmentioning
confidence: 99%
“…Given that data exist prior to their analysis and are not limited to a particular constellation of technologies, we consider "data ethics" as a bridge between these related fields. While this paper will not delve into the subtle overlaps and important distinctions between these unique fields of research and education, we acknowledge these distinctions and suggest the following literature for further insight (Fiesler et al, 2020;Hao, 2021;Metcalf et al, 2015;Nkonde and Patton, 2021;Ochigame, 2019;Raji et al, 2021;Sloane, 2019;Taylor, 2017;Thomas and Wiggins, 2019;Zeffiro, 2021).…”
Section: Background and Related Workmentioning
confidence: 97%
“…Research with human participants in Canada is governed by the federal government's Tri‐Council Policy Statement for Ethical Conduct of Research Involving Humans (2018). In a recent review of the ethics documents that regulate research in specific Canadian universities, Zeffiro (2021) found that not a single institution (including our own) provided ethical guidance for research that relies on social media data; they all referred researchers to Tri‐Council guidelines, which we consulted for direction on the ethical dimensions of employing YouTube vlogs as a data source. Those guidelines categorize vlogs as non‐intrusive web‐based data in that there is no direct, engaged interaction between researcher and participants and participants post videos in the public domain with no expectation of privacy.…”
Section: Concerns Related To Using Vlogsmentioning
confidence: 99%